Suchman’s legitimacy strategies evidenced by brazilian companies addressing the appllying for of Carbon Disclosure Project - Farias, Luana das Graças Queiroz de; Andrade, José Célio Silveira; Gomes, Sônia Maria Silva (Revista de Administração da UFSM, 2017)
This article is the result of a doctoral dissertation based on exploratory research and 10 case studies. The Carbon Disclosure Project/Investors in Brazil is the empirical research object of this article. Since its creation in 2000, this program has been playing an important role, related to the disclosure of social and environmental information. It has aimed at improving the transparency upon climate change risks and opportunities. This study identified Suchman’s legitimacy strategies (1995) that are most used by Brazilian companies, which have addressed the applied for Carbon Disclosure Project (CDP) between 2006 and 2010. Qualitative approach and content analysis technique were adopted in order to collect the data. The primary data were obtained through the application of a survey and the secondary data were obtained in institutional websites, CDP’s reports and records on emissions collected by Fundação Getulio Vargas. All Suchman’s legitimacy strategies were found in this study. The pragmatic strategy and the gain criteria obtained the biggest number of occurrences, 377 and 495 respectively. The most frequent cited item in all the 10 case studies was the necessity to respond to stakeholders, represented by 335 citations. Finally, it is possible to conclude that the CDP has been considered, by Brazilian companies, as a tool to obtain stakeholders’ acceptance and legitimacy.